Homologous minicircles in Leishmania donovani - Lambson, B.; Barker, D.C. (Oxford University Press, 2002)
Leishmania minicircular deoxyribonucleic acid (DNA) is arranged into different classes according to sequence. These classes differ substantially in sequence, despite species- and genus-specific regions, and are present in widely different copy numbers within and between Leishmania strains. Homologous minicircles have been identified in different species of Leishmania by comparing sequences of known minicircles. However, it is possible to select for minicircles of the same class by amplifying Leishmania DNA with polymerase chain reaction primers from the conserved and variable regions. This approach was used with 2 different minicircle classes in the L. donovani complex. In all isolates tested it was possible to amplify minicircles of the selected class.